Indentifikasi Tingkat Kesehatan dan Stres Kelelawar Pemakan Buah (Cynopterus Titthaecheilus) (IDENTIFICATION OF HEALTH AND STRESS LEVEL OF FRUIT EATING BATS (CYNOFTERUS TITTHAECHEILUS)) - Rahma, Anisa; Hanadhita, Desrayni; Prawira, Andhika Yudha; Cahyadi, Danang Dwi; Supratikno, Supratikno; Maheshwari, Hera; Satyaningtijas, Aryani Sismin; Agungpriyono, Srihadi (Jurnal Veteriner; Vol 19 No 4 (2018)DO - 10.19087/jveteriner.2018.19.4.460, 2019)
Hematology value is important to evaluate individual health status. This study was purposed to observe the hematological values of male and female Cynopterus titthaecheilus. The study was conducted on 16 C. titthaecheilus (six adult males, six adult females and four juveniles) to study the haematological profiles. Blood samples were taken using tuberculin needles and analyzed by hematology analyzer for hematological values. Females C. titthaecheilus had a higher number of white blood cells than the males, but no differences in the white blood cells differential. Males C. titthaecheilus had a higher number of platelets than the females. Generally, the juveniles had a higher number of leucocytes as well as number of platelets than the adults. Based on the stress index value, it was concluded that young bats had a lower stress level compared to adult bats.
Keywords: flying mammals, leukocyte differentiation, platellet, stress indeks